Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Complex Integration: Line Integrals

Download as pdf or txt
Download as pdf or txt
You are on page 1of 8

Complex integration

Line integrals:
(𝟐,𝟒)
1.Evaluate ∫(𝟎,𝟑) {(𝟐𝐲 + 𝐱 𝟐 )𝐝𝐱 + (𝟑𝐱 − 𝐲)𝐝𝐲} along (a) the parabola
x=2t, 𝒚 = 𝐭 𝟐 + 𝟑, (b)Straight line from (0,3) to (2,3) and then from
(2,3) to (2,4) (c) a straight line from (0,3) to (2,4)
(𝟐,𝟒)
Solution: Given that, ∫(𝟎,𝟑) {(𝟐𝐲 + 𝐱 𝟐 )𝐝𝐱 + (𝟑𝐱 − 𝐲)𝐝𝐲}

(a)The points (0,3) and (2,4) on the parabola correspond to t=0 and Here,
t=1 respectively. Then the given integral equals 𝐱 = 𝟐𝐭
(𝟐,𝟒)
𝐝𝐱 = 𝟐𝐝𝐭
𝐲 = 𝐭𝟐 + 𝟑
∫ {(𝟐𝐲 + 𝐱 𝟐 )𝐝𝐱 + (𝟑𝐱 − 𝐲)𝐝𝐲} 𝐝𝐲 = 𝟐𝐭𝐝𝐭
(𝟎,𝟑)

= ∫[{𝟐(𝐭 𝟐 + 𝟑) + 𝟒𝐭 𝟐 } 𝟐 𝐝𝐭 + {𝟑. 𝟐𝐭 − (𝐭 𝟐 + 𝟑)} 𝟐𝐭 𝐝𝐭]


𝐭=𝟎

= ∫[{(𝟐𝐭 𝟐 + 𝟔) + 𝟒𝐭 𝟐 } 𝟐 𝐝𝐭 + {𝟔𝐭 − (𝐭 𝟐 + 𝟑)} 𝟐𝐭 𝐝𝐭]


𝐭=𝟎

= ∫(𝟒𝐭 𝟐 + 𝟏𝟐 + 𝟖𝐭 𝟐 + 𝟏𝟐𝐭 𝟐 − 𝟐𝐭 𝟑 − 𝟔𝐭) 𝐝𝐭


𝐭=𝟎

= ∫(𝟐𝟒𝐭 𝟐 + 𝟏𝟐 − 𝟐𝐭 𝟑 − 𝟔𝐭) 𝐝𝐭
𝐭=𝟎
1 1 1
 t3  t4  t2
 3   12t   2 4   6 2 
1
 24
0
  0     0 0

𝟏
=8(1-0)+ 12(1-0) - (1-0) – 3(1-0)
𝟐
𝟑𝟑
=
𝟐

(b)Along the straight line from (0,3) to Again along the straight line from (2,3)
(2,3), y=3,dy=0 and the line integral to (2,4), x=2,dx=0 and the line integral
equals equals
(2,3) (2,4)

∫ {(2y + x 2 )dx + (3x − y)dy} ∫ {(2y + x 2 )dx + (3x − y)dy}


(0,3) (2,3)

2 4
= ∫x=0(6 + x 2 )dx = ∫y=3(6 − y)dy

2 2

 
4
= ∫x=0 6dx + ∫x=0 x 2 dx 4  y2 
= 6y 3 -  
 2
 
2
2 x3  3

= 6x 0 +  
3 = 6(4 − 3) −
1
2
(42 − 32 )
0
1 3 8
= 6(2 − 0) + (2 − 0) = 12 + 7 5
3 3
44 =6 - =
2 2
=
3
(c)An equation for the line joining (0,3) to 𝐱 − 𝐱𝟏 𝐲 − 𝐲𝟏
=
(2,4) is x = 2y – 6. dx = 2dy.Then the line 𝐱𝟏 − 𝐱𝟐 𝐲𝟏 − 𝐲𝟐
integral equals
(𝟐,𝟒) 𝐱−𝟎 𝐲−𝟑
𝟎𝐫, =
∫ {(𝟐𝐲 + 𝐱 𝟐 )𝐝𝐱 + (𝟑𝐱 − 𝐲)𝐝𝐲} 𝟎−𝟐 𝟑−𝟒
(𝟎,𝟑)
𝟒 𝐱−𝟎 𝐲−𝟑
= ∫ [{𝟐𝐲 + (𝟐𝐲 − 𝟔)𝟐}𝟐𝐝𝐲 + {𝟑(𝟐𝐲 − 𝟔) − 𝐲}𝐝𝐲] 𝟎𝐫, =
−𝟐 −𝟏
𝐲=𝟑

𝟒 𝐱−𝟎 𝐲−𝟑
𝟎𝐫, =
= ∫ [{𝟐𝐲 + 𝟒𝐲 𝟐 − 𝟐𝟒𝐲 + 𝟑𝟔}𝟐𝐝𝐲 + {(𝟔𝐲 − 𝟏𝟖) − 𝐲}𝐝𝐲] 𝟐 𝟏
𝐲=𝟑

𝟎𝐫, 𝐱 = 𝟐𝐲 − 𝟔
𝟒

= ∫ [𝟒𝐲 + 𝟖𝐲 𝟐 − 𝟒𝟖𝐲 + 𝟕𝟐 + 𝟓𝐲 − 𝟏𝟖]𝐝𝐲


𝐲=𝟑

= ∫ [𝟖𝐲 𝟐 − 𝟑𝟗𝐲 + 𝟓𝟒]𝐝𝐲


𝐲=𝟑

54 y
4 4
 y 3
y 2 4
= 8  39
-  + 3
 3   2  3 3

8 39 2
= (43 − 33 ) − (4 − 32 ) + 54(4 − 3)
3 2

97
=
6
2.Evaluate ∫𝐜 𝐳̅ 𝐝𝐳 from z=0 to z = 4+2i along the curve C given by (a)
𝒛 = 𝐭 𝟐 + 𝐢𝐭, (b) the line from z=0 to z = 2i and then the line from z = 2i
to z = 4+ 2i.

Solution: The given integral equals

∫c z̅ dz =  ( x  iy )( dx  idy ) =  xdx  ixdy  iydx  ydy =  xdx  ydy +i


c c c

 xdy  ydx
c

The parametric equations of C are 𝒙 = 𝐭 𝟐 ,dx=2tdt, y = t,dy=dt from


t=0 to t = 2 .Then the line integral equals
𝟐 𝟐
∫𝐭=𝟎 𝐭 𝟐 . 𝟐𝐭𝐝𝐭 + 𝐭𝐝𝐭 + i ∫𝐭=𝟎 𝐭 𝟐 𝐝𝐭 − 𝐭. 𝟐𝐭𝐝𝐭
𝟐 𝟐
= ∫𝐭=𝟎(𝟐𝐭 𝟑 + 𝐭)𝐝𝐭 + i ∫𝐭=𝟎(𝐭 𝟐 − 𝟐𝐭 𝟐 )𝐝𝐭
𝟐 𝟐
= ∫𝐭=𝟎(𝟐𝐭 𝟑 + 𝐭)𝐝𝐭 - i ∫𝐭=𝟎 𝐭 𝟐 𝐝𝐭
2 2 2
 4  2  3
= 2 t  +  t  - i  t 
 4 2 0 0 3 0

𝟏 𝟏 𝟏
= (𝟐𝟒 − 𝟎) + (𝟐𝟐 − 𝟎) − 𝐢 (𝟐𝟑 − 𝟎)
𝟐 𝟐 𝟑
𝟖𝐢 𝟖𝐢
= 𝟖+𝟐− = 𝟏𝟎 −
𝟑 𝟑
(b)The given line integral equals

 ( x  iy )(dx  idy ) =  xdx  ydy + i c xdy  ydx


c c

The line from z=0 to z=2i is the same as the line from(0,0) to(0,2) for
which x=0,dx=0 and the line integral equals
2 2

 (0)(0)  ydy + i  (0)dy  y(0)


y 0 y 0

=  ydy
y 0

=2

Again the line from z=2i to z=4+2i is the same as the line from(0,2)
to(4,2) for which y=2,dy=0 and the line integral equals
4 4

 xdx  2.0 + i  x.0  2dx


x 0 x 0

4 4
=  xdx - i  2dx
x 0 x 0

= 8 – 8i

Then the required value = 2+8-8i = 10-8i

3.(HW) Evaluate ∫ 𝐳 𝟐 𝐝𝐳 along (i) the line segment joining the points
(1,1) and (2,4) (ii) the curve x = t, y = 𝐭 𝟐 joining the points (1,1) and
(2,4)
𝟏+𝐢
4. Evaluate ∫𝟎 (𝐳 𝟐 + 𝐳)𝐝𝐳 .By choosing two different paths of
integration show that the results are same.

Solution: Given that the integral


𝟏+𝐢

∫ (𝐳 𝟐 + 𝐳)𝐝𝐳
𝟎

Let us choose two paths 𝐂𝟏 and 𝐂𝟐 as shown in the figure:

Y B(1+i)
C2
C1

C1 A(1,0)
X

First we consider the path 𝐜𝟏


𝟏+𝐢 𝟏 𝟏

∴ ∫ (𝐳 𝟐 + 𝐳)𝐝𝐳 = ∫(𝐱 𝟐 + 𝐱)𝐝𝐱 + ∫[(𝟏 + 𝐢𝐲)𝟐 + (𝟏 + 𝐢𝐲)]𝐢𝐝𝐲


𝟎 𝟎 𝟎

[∵ 𝐨𝐧 𝐱 − 𝐚𝐱𝐢𝐬 𝐳 = 𝐱 𝐚𝐧𝐝 𝐨𝐧 𝐭𝐡𝐞 𝐥𝐢𝐧𝐞 𝐀𝐁, 𝐳 = 𝟏 + 𝐢𝐲 ⇒ 𝐝𝐳 = 𝐢𝐝𝐲]

 1 iy  1 iy


1
1
2
 3 2 3
= x  x  + i   
3 2 0  3i 2i  0
𝟏 𝟏 (𝟏+𝐢)𝟑 (𝟏+𝐢)𝟐 𝟏 𝟏
=( + ) + i [( + ) − ( + )]
𝟑 𝟐 𝟑𝐢 𝟐𝐢 𝟑𝐢 𝟐𝐢

𝟓 𝟏+𝟑𝐢+𝟑𝐢𝟐 +𝐢𝟑 𝟏+𝟐𝐢+𝐢𝟐 𝟏 𝟏


=( ) + [( + ) − ( + )]
𝟔 𝟑 𝟐 𝟑 𝟐

𝟓 𝟏+𝟑𝐢−𝟑−𝐢 𝟏+𝟐𝐢−𝟏 𝟓
=( ) + [( + ) − ( )]
𝟔 𝟑 𝟐 𝟔

𝟐𝐢−𝟐
= ( + 𝐢)
𝟑

𝟐𝐢 − 𝟐 + 𝟑𝐢
=
𝟑
𝟓𝐢 − 𝟐
=
𝟑

𝟓𝐢 𝟐
∴ ∫ (𝐳 𝟐 + 𝐳)𝐝𝐳 = −
𝟑 𝟑
𝐂𝟏

Now we consider the path 𝐂𝟐

Let z = (1+i)t, 𝟎 ≤ 𝐭 ≤ 𝟏.Then dz = (1+i)dt


𝟏

∴ ∫ (𝐳 𝟐 + 𝐳)𝐝𝐳 = ∫[(𝟏 + 𝐢)𝟐 𝐭 𝟐 + (𝟏 + 𝐢)𝐭](𝟏 + 𝐢)𝐝𝐭


𝐂𝟐 𝟎

𝟏 𝟏

= ∫(𝟏 + 𝐢)𝟑 𝐭 𝟐 𝐝𝐭 + ∫(𝟏 + 𝐢) 𝟐 𝐭𝐝𝐭


𝟎 𝟎

1 1

𝟑 t3  𝟐 t 2 
= (𝟏 + 𝐢)   +(𝟏 + 𝐢)  
3 2 0 0
𝟏 𝟏
= (𝟏 + 𝐢)𝟑 ( − 𝟎) + (𝟏 + 𝐢)𝟐 ( − 𝟎)
𝟑 𝟐
𝟏 + 𝟑𝐢 + 𝟑𝐢𝟐 + 𝐢𝟑 𝟏 + 𝟐𝐢 + 𝐢𝟐
= +
𝟑 𝟐
𝟏 + 𝟑𝐢 − 𝟑 − 𝐢 𝟏 + 𝟐𝐢 − 𝟏
= +
𝟑 𝟐
𝟐𝐢 − 𝟐
= +𝐢
𝟑
𝟓𝐢 − 𝟐
=
𝟑

𝟓𝐢 𝟐
∴ ∫ (𝐳 𝟐 + 𝐳)𝐝𝐳 = −
𝟑 𝟑
𝐂𝟐

You might also like